Acinetobacter ursingii Bacteremia From a Peripherally Inserted Central Catheter in a Woman With Hyperemesis Gravidarum. Issue 5 (September 2016) - Holloman, Conisha; Franco, Arielle; Carlan, Stephen J.; Busowski, Mary; Busowski, John
Abstract : Background: Hyperemesis gravidarum is defined as severe nausea and vomiting of pregnancy associated with weight loss and dehydration if left untreated. Treatment will sometimes require the placement of a peripherally inserted central catheter line for the administration of intravenous antiemetics, total parenteral nutrition, and rehydration. Acinetobacter ursingii is a nonmotile, aerobic, gram-negative coccobacilli that are widespread in natural moist environments and are rarely isolated as a definitive human pathogen. Case: We present a case of a previously healthy immunocompetent pregnant woman in the second trimester with a peripherally inserted central catheter line placed for the management of hyperemesis gravidarum who subsequently developed bacteremia with A. ursingii. The patient was treated with intravenous meropenem and oral ciprofloxacin. Conclusions: Central catheters are a risk factor for sepsis with A. ursingii in immunocompetent pregnant women, and aggressive treatment with appropriate antibiotics should be implemented.